Nanoscale controlled architecture for development of ultrasensitive lectin biosensors applicable in glycomics - Kluková, L. (Anal Methods, 2014)
In this Minireview the most advanced patterning protocols and transducing schemes for development of ultrasensitive label-free and label-based lectin biosensors for glycoprofiling of disease markers and some cancerous cells are described. Performance of such lectin biosensors with interfacial properties tuned at a nanoscale are critically compared to the most sensitive immunoassay format of analysis and challenges ahead in the field are discussed. Moreover, key elements for future advances of such devices on the way to enhance robustness and practical applicability of lectin biosensors are revealed.